PENGEMBANGAN EPISTEMOLOGI REALISME MELALUI PRINSIP-PRINSIP KULTURAL - Uhi, Jannes Alexander (Faculty of Humanities, Diponegoro University, 2011)
Humanism needs a fundamental and realistic epistemological foundation. A realistic epistemological foundation is a part of implementing cultural principles of a society which is itself a part of the reformulation process of realism epistemology. This effort to reformulate realism epistemology always pays a good attention to cultural reality in the society as an important element. Cultural reality essentially reflects humanity values and they can be employed as a strong foundation of contemporary epistemological development. By referring to cultural reality, epistemology may be developed effectively and usefully. The strength of this kind of epistemological development may position humanism not only as some knowledge, but as a well-developed culture in the society as well. Â Keywords: epistemologi realism, culture, humanism.